(untitled) (Global Journal of Human-Social Science, 2018)
An approximately 54.4 million people or 17.7% of the U.S population live in areas without nutritious food outlets, have low access to a vehicle and have challenges accessing a nutritious food outlet. The lack of access to nutritious food outlets mainly affects low-income residents of both urban and rural areas and remains a challenge because the deprived residents mostly depend on innutritious food outlets such as neighborhood convenience stores, which can be detrimental to their health. Researchers of varying disciplines have examined the problem of food access, however, in a piecemeal nature. This paper, therefore, critically examines research across two disciplines concerned with food accessibilitygeography and public health to create a more comprehensive approach to food accessibility research based on their perspectives and approaches. Although some dissimilarities exist between the perspectives and approaches employed in food accessibility research by the two disciplines, common grounds are established via the identification of the concept of place and socio-economic characteristics of people as the main driving factors of food accessibility research among the disciplines. These perspectives are integrated along the common driving elements to form an interdisciplinary research approach and construct a comprehensive understanding of the problem of food accessibility.